ELIMINATION OF ELECTRICAL ENERGY WASTE IN RESIDENTIAL BUILDINGS OF 10-04 SQUARE METERS - Qosimov Oybek, (Лучшие интеллектуальные исследования, 2024)
Abctrakt: In this article, you can get general information about the project, how to create the project , and why the project was created. Information about the first stages of project development, the necessary conditions for 10 and 0.4 kV projects in residential areas is also provided. The basic concepts of electrical design and design are presented.